Development Of Risk-Based Audit Method Standard For Stadium Project Using Design And Build Contract To Minimize Dispute From Construction Management Point Of View - Alvian Sutekat, Ega; Putro, Anggoro; Latief, Yusuf (International Journal of Science, Technology & Management, 2023)
The Design and Build method have been widely used in government projects in recent years. The construction of a sports stadium is one type of project that uses an integrated contract. Design and build, which is considered to have high complexity and is urgent, so the use of the Design and Build method is expected to provide a solution in the implementation of the project. However, in implementing the integrated design and construction contract, there are still many disputes from stakeholders involved such as Inspection of Work Results. This study aims to identify the factors that cause dispute in the Design and Build project and develop a Standard for Inspection of Work Results from the perspective of Construction Management. The results of the study indicate the factors causing the dominant risk-based dispute as well as corrective action in the form of standard inspection of work results on construction projects.